Origem, ascensão e crise do Fies: uma análise regional do Programa de Financiamento Estudantil do Ensino Superior para o período de 2011 a 2018 - Rebêlo, Ana Carolina Monteiro (2019)
In the world economic scenario, there is a clear heterogeneity in the level of countries’ development, which has aroused the interest of many economists to the study of growth and economic development, in order to know the causes of this growth. Also, at the national level, in the vast majority of countries, especially in developing countries such as Brazil, there is heterogeneity of development among their regions. Human capital, despite being more prominent in the 1960s, has always been present in the theories of economic growth as one of the fundamental factors for this process, along with the formation of physical capital and technological innovation. In this sense, higher education stands out, given its characteristic of training specialized professionals, to foment research and technological innovation. In Brazil, the creation of the Student Financing Program for Higher Education (Fies), institutionalized in 2001, aimed to encourage the qualification of the work force, mainly in the North, Northeast and Central West regions, considered less developed and more in need of this qualification. However, there are possible ramifications of this program that can bring losses in the medium and long term to the whole country, especially in the sense of accentuating regional inequalities. Thus, the objective of this work is to analyze the implications of the distribution of FIES resources in the context of regional development, from 2011 to 2018. The data come from the digital platforms of FNDE and INEP. Therefore, we will recover some of the theories of growth and economic development, as well as the theory of human capital, then we will make a historical summary of higher education in Brazil, addressing some realities of public and private higher education, herewith a brief description of the appearance of Fies. Next, we will describe the development and crisis of Fies, concluding with the analysis of its regional distribution through the Shift-Share method between the period of 2011 to 2018, since it corresponds to the time interval for which data are available.